Thermoluminescent and Dosimetric Properties of Zirconium Dioxide Ceramics Irradiated with High Doses of Pulsed Electron Beam - Nikiforov, Sergey; Dauletbekova, Alma; Gerasimov, Maksim; Kasatkina, Yana; Denisova, Olga; Lisitsyn, Viktor; Golkovski, Mikhail; Akylbekova, Aiman; Bazarbek, Assyl-Dastan; Akilbekov, Abdirash; Popov, Anatoli I. (MDPI, 2023)
Thermoluminescent (TL) properties of monoclinic zirconium dioxide ceramics were studied in order to assess the possibility of their use for measuring high doses (on the order of kGy) of pulsed electron beams (130 keV). Two types of samples were used: those synthesized by sintering in an electric furnace at T = 700–1700 °C and those synthesized in a flow of high-energy electrons (1.4 MeV) with a high power density. Analysis of the X-ray diffraction patterns using the Scherrer method revealed that annealing of ceramics of the first type at T > 1000 °C leads to a significant increase in the size of crystallites, which correlates with a significant increase in the intensity of the TL peak at 390 K. Type 2 ceramics synthesized by the electron beam method have the maximum TL response. Using the peak shape analysis method, the kinetic parameters of TL (activation energy, frequency factor, and kinetic order) were calculated. This study marks the first instance of establishing the patterns of influence of synthesis conditions and crystallite size on their values. The presence of an intense isolated TL peak, the sublinear nature of most dose dependencies, and negligible fading indicate the promise of the ceramics synthesized in this work for measuring high doses (several to tens of kGy). --//-- This is an open-access article Nikiforov, S.; Dauletbekova, A.; Gerasimov, M.; Kasatkina, Y.; Denisova, O.; Lisitsyn, V.; Golkovski, M.; Akylbekova, A.; Bazarbek, A.-D.; Akilbekov, A.; et al. Thermoluminescent and Dosimetric Properties of Zirconium Dioxide Ceramics Irradiated with High Doses of Pulsed Electron Beam. Crystals 2023, 13, 1585. https://doi.org/10.3390/cryst13111585 published under the CC BY 4.0 licence.
Latvian Council of Science grant LZP-2021/1-0464 and the State Program for Scientific Research of Belarus “Photonics and Electronics for Innovations” (subprogram “Photonics and its application”, task 1.8; subprogram “Opto- and microwave electronics, task 2.2).
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; thermoluminescent properties; dosimetric properties; zirconium dioxide ceramics; high-energy electrons